Chair design for older immobile people: Comparison of pressure mapping and manual handling outcomes. (January 2022) - Champion, Stephanie; Barr, Christopher; Lange, Belinda; Lewis, Lucy K.; Russo, Michael P.; Maeder, Anthony; Gordon, Susan
Abstract: The number of older adults unable to transfer or ambulate independently is increasing. High support chairs enable people experiencing loss of mobility to be mobile, but current chair designs are associated with global functional loss and pressure ulcers. This pilot study compared the functionality of a traditional design high support chair to a new design of motorised high support chair: 1) a motion laboratory study compared joint angles and pressure at the hip, knee, ankle, elbow and spine when pushing each chair, and 2) a pressure mapping study compared the interface pressure when older people with limited mobility used the chairs. Significant reduction in joint angles for the person pushing the chair (degree difference range −3.6 to 14.2) and decreased seated pressure (w/kg difference range −0.2 to 2.1) for the seated user were identified for the motorised chair. Longitudinal investigations are required to determine if the significant differences identified in this pilot study result in less manual handling injuries and pressure areas.